Textbook of endodontology - Bj??rndal, Lars (New Delhi : Elsevier, 2010)
Textbook of Endodontology, 3rd Edition is an invaluable reference for dental students and dental practitioners seeking an introduction to, or update on, endodontic theories and techniques. Restructured and completely updated, the new edition maintains the ethos of the original, facilitating ease of learning through pedagogical features such as annotated references, core concepts and key literature. It includes a number of new chapters on topics ranging from local anaesthesia to medico-legal considerations--Provided by publisher.
Includes bibliographical references and index.
Keywords: Dental Pulp Diseases; Periapical Diseases